Jurgen Habermas's views on legal validity and discourse ethics: A literature review - Febriani, Rika; Supartiningsih, Supartiningsih; Tjahyadi, Sindung (Universitas Negeri Yogyakarta, 2025)
In modern states, law is often reduced to merely a tool of power. Many contemporary practices treat law as nothing more than a procedural requirement, disregarding its substantive values and the social conditions of society. This article discusses the validity of law within a political community from Habermas's perspective. According to him, the law must be discursive and stem from rational subjects capable of effective communication. The fundamental questions addressed are: how can law ideally be derived from norms within a political society? And how can law subsequently foster a democratic society? This article employs historical-factual methods, with primary sources drawn from the works of Jí¼rgen Habermas. Habermas used discourse ethics and the theory of communicative action. Data collection is conducted through textual analysis. The article concludes that the validity of law must originate from discursive norms present in society, even though there may be tensions between theory and practice in society.